Pengaruh Perbedaan Jarak Tanam terhadap Pertumbuhan Tiga Varietas Kedelai (Baluran, Bromo, dan Galunggung) - Djukri, Djukri (Universitas Atma Jaya Yogyakarta, 2005)
The objective of the research was to investigate the effect of sunlight radiation distribution in canopy on soybean plants biomass at different planting distances. This research was done experimentally using the Block Design. The independent variables were the soybean varieties and planting distance. The varieties used were Baluran, Bromo, and Galunggung and the planting distance used was 15x15 cm2 and 25x25 cm2 as blocks with 10 replications. The dependent variables were sunlight intensity and the plants biomass. The result of the research indicated that after 40 planting days, the sunlight intensity in the canopy, at soybean varieties factors was significant (p<0.05), and the planting distance was significant too. The plant biomass indicated that varieties factors had a significant effect (p<0.05), but the planting distance factors were not significant (p>0.05).